Impact of static biocarriers on the microbial community, nitrogen removal and membrane fouling in submerged membrane bioreactor at different COD:N ratios. (April 2020) - Wang, K.M.; Jiang, S.F.; Zhang, Z.H.; Ye, Q.Q.; Zhang, Y.C.; Zhou, J.H.; Hong, Q.K.; Yu, J.M.; Wang, H.Y.
Graphical abstract: Highlights: Biocarrier addition can effectively reduce membrane fouling even at low C/N ratio. Bulk sludge is significantly improved with biocarrier to achieve low fouling. Denitrification bacteria accumulates in biocarrier and improves nitrogen removal. Biocarrier addition can partially overcome drawbacks of low C/N ratio. Abstract: The polyvinyl formal (PVFM) biocarrier addition in a membrane bioreactor (MBR) was evaluated at high and low carbon/nitrogen (C/N) ratio of 20.0 and 6.7. Results indicated that static biocarrier addition could enrich nitrification and denitrification bacteria, dominating by Tauera, Amaricoccus and Nitrosospira at the genus level and slightly improved the total nitrogen removal even at a low C/N ratio. The bulk sludge characteristics (such as bigger particle size, lower SMP, lower SMP P/C) were also significantly changed in the hybrid MBR (HMBR), leading to a more sustainable membrane operation. The biocarrier addition also reduced the relative abundance of Sphingobacterials_unclassified, Ohtaekwangia and Rhodocyclaceae_unclassified at the genus level, indicating less membrane fouling in the HMBR. Consequently, HMBR with static PVFM addition could partially overcome the drawback of low C/N ratio for total nitrogen removal and membrane fouling control, providing a more resilient MBR to the undesirable environment such as low C/N ratio.